COMPARISON OF BOOK VALUE AND AUCTION VALUE OF MEHSANA BUFFALOES DISPOSED AT AN ORGANIZED FARM (Indian Journal of Animal Production and Management, 2014)
An analysis was made on book value and auction value of Mehsana buffalo disposed at organized farm Livestock Research Station, S. D. Agricultural University, Sardarkrushinagar for the period of 05 years from 2009 to 2013. Total 72 buffaloes (36.55 %) were auctioned due to various reasons. The average book value, auction value and benefit over book value were Rs. 2616.42, Rs. 23387.67 and Rs. 20771.25 per buffalo. Highest benefit (Rs. 21640.00 per animal) was obtained from the animals disposed having reproductive disorders. Parity wise highest benefit has been gained from the animal having 5th parity (Rs. 26607.00 per animal). On an average benefit of Rs. 20771.00 per animal from the auction of 72 milch buffaloes was gained. The buffaloes disposed off due to various reasons was found significant (P
Keywords: Auction; Buffalo; Reason; Parity; Benefit